A Novel Design Method for Filter/Guidance Simulation System - Wang, Yu Zhe; Wang, Min; Xue, Hui Wen; Su, Hang (Applied Mechanics and Materials, 2015)
A filter/guidance simulation toolbox based on Matlab software was designed. Built under the principle of “define once and use many times”, the propose toolbox successfully separate the estimation algorithms, the guidance law, and the math model under investigation into three different yet related parts, which drastically reduced the burden of repeatedly designing the same filters and guidance law for different simulation models. Typical example from both simulation cases and real field test data proved the correctness and effectiveness of the proposed toolbox.